2009
DOI: 10.1111/j.1399-3046.2009.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life, treatment adherence, symptom experience and depression in adolescent renal transplant patients

Abstract: Few studies comprehensively assessed psychological and behavioral functioning in adolescent kidney transplant patients. The purpose of this cross-sectional study was to evaluate depression, QOL, treatment adherence and presence of side effects from the perspective of the patient and his parents, and to compare scores with norm data. All patients (age 10-18 yr) and their parents completed the following instruments: KIDSCREEN-27 (QOL), a treatment adherence interview, the MTSOSD-59R (side effects) and the Beck D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 21 publications
(29 reference statements)
3
82
2
5
Order By: Relevance
“…1,9,32 Our search for studies investigating the depression level in liver transplant patients after transplant demonstrated a gap in the literature. On the other hand, a study of kidney transplant patients demonstrated no depression in 82.6% of the patients, 7 which is similar to the rate (88%) determined in this present study. That there was no difference between the depression level of the case group patients and that of their healthy peers is a positive outcome.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…1,9,32 Our search for studies investigating the depression level in liver transplant patients after transplant demonstrated a gap in the literature. On the other hand, a study of kidney transplant patients demonstrated no depression in 82.6% of the patients, 7 which is similar to the rate (88%) determined in this present study. That there was no difference between the depression level of the case group patients and that of their healthy peers is a positive outcome.…”
Section: Discussionsupporting
confidence: 91%
“…In a study of adolescent kidney transplant patients (median age, 15 y), the most prevalent symptoms were increased appetite, fatigue, headache, pimples, trembling hands, increased thirst, lack of energy, mood swings, flatulence, and warts on the hands or feet. 7 That these symptoms were different from the symptoms observed in our patients can be explained by the use of different immunosuppressants in the liver transplant. In our study, the patients experienced all the psychological symptoms included in the MTSOSD-58.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Total score of each part was similarly obtained by adding those of the individual items, and a larger score referred to more distresses of side effects. If the occurring frequency of a specific side effect of a patient was reported as "not at all" (0 point), the corresponding symptom distress would not be included in the statistical analysis as the missing data [11,12].…”
Section: Modified Transplant Symptom Occurrence Andmentioning
confidence: 99%